Identificação dos principais autores do planejamento e controle de produção (PCP) e análise da lacuna entre a teoria e a prática do PCP na região de São Carlos. - Azeka, Fábio (2003)
This research have two main goals: i) the Production Planning and Control (PPC) top-authors identification according to an effective population (EF)with 592 international researchers; and ii) assessing the gap between theory and practice on the PPC area at São Carlos region. To determine the item (i) it was done a research through internet with an initial sample of 205 researchers, as not all e-mails worked, the effective sample (ES) was reduced to 168 researchers. The obtained result was estimated for the corrected effective population (CEP), that corresponds to the number of people whose e-mails worked, through the Horwitz-Thompson estimator. At the end of this stage we obtained a list containing the top-authors of the area and their main works as well as we accomplished analysis involving variables like the region, the approach and the number of years the respondents are active on PPC research. To accomplish the item (ii) we collected data from a group of São Carlos academics and from 11 important companies of the region. We lifted up several causes of the existence of this gap in the area and we also suggested several initiatives to decrease it.